Hubungan Ketebalan Lemak Dengan Fleksibilitas Trunkus Remaja Putri - Bambang Trisnowiyanto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Fat Thickness, Flexibility Trunks. The purpose of this study to determine the thickness of fat on the trunk flexibility in adolescent girls. The flexibility of the body is a person's ability to perform activities with the widest stretch especially the muscles and ligaments around the joints of the body. The ability of flexibility in the lumbar region known to affect the working system of the human body, especially in conducting activities related to body curvature. Individuals who have a lot of folds of fat in various segments of the body will affect the ability of the flexibility of the trunk. This research method using a descriptive correlation between variables. Research instrument with skinfold caliper for fat thickness and fingertip to the floor for the trunk flexibility. Test the relationship between the thickness of the fat with the flexibility of the trunk with Spearman p = 0.000 (p <0.05) showed a significant correlation, r = -0,720 with the direction of the negative correlation. Conclusion there is a relationship between the thickness of body fat to the flexibility of the trunk in adolescent daughter